A time to consider, a time to deliver: The independent and interactive effects of regulatory mode on innovative work behavior. Issue 2 (23rd February 2022) - Liu, Haixin; Rubenstein, Alex L.; Li, Guiquan; Liu, Zhaoyan; Zhan, Xiaojun; Xiong, Jie
Abstract: Although innovative work behavior (IWB) is essential to organizational success and survival, little is known about its dispositional antecedents. In this study, we invoke regulatory mode theory to examine the independent and interactive effects of two regulatory orientations, assessment and locomotion, on three aspects of employee IWB: idea generation, promotion, and realization. Results from lagged survey data generally supported our hypotheses that each orientation would exhibit distinct effect patterns. For idea generation, assessment exhibited a positive relationship, whereas locomotion exhibited a negative relationship. Meanwhile, only locomotion was significantly (positively) related to idea promotion. And for idea realization, both assessment and locomotion exhibited positive associations. Furthermore, the interaction of assessment and locomotion in relation to each aspect of IWB also revealed distinct patterns: for idea generation, higher levels of assessment buffered against the negative effects of locomotion; for idea promotion, higher assessment constrained the positive effects of locomotion; and for idea realization, assessment supported locomotion, such that we observed greater realization levels when both regulatory modes were higher. We discuss the theoretical and practical implications of our results, as well as promising directions for future research concerning both regulatory mode and IWB.